PKM di Kabupaten Karawang: Pendampingan Penggunaan Aplikasi Pendekatan SKD Berbasis CAT - Sari, Dessy Agustina; Sukanta, Sukanta; Hakiim, Azafilmi (Buletin Udayana Mengabdi; Vol 19 No 3 (2020): Buletin Udayana Mengabdi, 2020)
State university in Kabupaten Karawang also celebrated the CPNS test in 2018 as initial for both lecturer and staff of education schemes. Many activity amounts of lecturers in Unsika caused training, which led LP3M (especially TIU) were ignored. The time of this coaching generally crushed their schedule in daily work, whereas the holiday time was not operated. The reason was not operational work for the government institute. By supported Sekai Elite Galuhmas Karawang and Vision Center Bandung, organizer the implementation activity presented workshop. It related to the necessity of introduction and test simulation of the CPNS, which based on CAT. Searching of the participant was obtained by spreading leaflets through the Whatsapp group, set the banner, and advertisement in Karawang’s newspaper. This thing gave achievement to 60 interested humans. From the keynote speakers’ explanation could be taken statements commonly that the participants had weakness in TIU than TWK and TKP. Nevertheless, the participants should give priority a higher score in TKP, then TIU, and the last TWK. It has passed over the passing grade, which ruled by Menpan each year.